HUMAN TALENT MANAGEMENT AND DIGITAL TEACHING COMPETENCE, ACCORDING TO THE PERCEPTION OF FIFTH HIGH SCHOOL STUDENTS IN EDUCATIONAL INSTITUTIONS OF THE NETWORK 11-CALLAO - GORDILLO-TORRES, Rosaura (2024)
The study in question proposed as a goal determine the correlation between “human talent management” and teaching “digital competence”, it is quantitative research, it correlates, we worked with a sample of 300 participants, the deductive method was used. The following were evident in the results. Deficiencies were found in managing the strengths that the workers of the intervened institutions have, firstly, they had an impact on their ways of organizing such as evaluations, being motivated, well treated and on stimulation for their performances. Also not encouraging results, referred to the organization of educational institutions and collaborative work, also on the issue of the search for educational quality, teacher training and how to evaluate through digital tools.